2013
DOI: 10.1016/j.febslet.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The HBx protein of hepatitis B virus confers resistance against nucleolar stress and anti‐cancer drug‐induced p53 expression

Abstract: a b s t r a c tThe nucleolus is a stress sensor associated with cell cycle progression and a viral target. However, the role of the nucleolus during hepatitis B virus infection has not been studied. Here we show that under nucleolar stress, the HBx oncoprotein down-regulates p53 and p21 waf1 levels by disrupting the interaction between ribosomal protein L11 and MDM2. Further, HBx inhibited Act D-mediated down-regulation of proliferat ive factors such as c-Myc and cyclin E and revived RNA pol I-dependent transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…Several previous studies found that HBx induced multiple chemotherapeutic drugs resistance through regulating various signaling factors, such as p53 and NF-ĸB (7,26,27). In our present study, the drug resistance activity induced by HBx was consistent with the results of several previous studies (7,26,27); we identified that signaling pathways involving RhoA, ROCK1 and p38 MAPK are associated with HBxinduced autophagy. In addition, UA, a pentacyclic triterpenoid acid known to possess a hepatoprotective function, demonstrated a suppression effect on HBx.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several previous studies found that HBx induced multiple chemotherapeutic drugs resistance through regulating various signaling factors, such as p53 and NF-ĸB (7,26,27). In our present study, the drug resistance activity induced by HBx was consistent with the results of several previous studies (7,26,27); we identified that signaling pathways involving RhoA, ROCK1 and p38 MAPK are associated with HBxinduced autophagy. In addition, UA, a pentacyclic triterpenoid acid known to possess a hepatoprotective function, demonstrated a suppression effect on HBx.…”
Section: Discussionsupporting
confidence: 92%
“…UA. Previous studies found that HBx endowed multiple chemotherapeutic drugs resistance through modulation of various cellular factors, for example, p53 tumor suppressor and NF-ĸB (7,26,27). To further understand the therapeutic potential of UA, the drug sensitivity IC 50 was evaluated in Huh7 cells treated with three anti-cancer DNA-damage agents in clinical use.…”
Section: Reversion Of Hbx-mediated Dna-damage Drug Resistance Bymentioning
confidence: 99%
“…The modifications of RPs that are involved in the RPs–MDM2–p53 pathway deserve further exploration. Interestingly, the HBx (Hepatitis B virus X) oncoprotein confers nucleolar stress induced p53 expression by disrupting the interaction between L11 and MDM2, suggesting the possible inactivation of the L11–MDM2–p53 pathway by the HBx oncoprotein in hepatocellular carcinogenesis. However, the relationship between defective ribosome biogenesis and cancer is complicated and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in addition to their role in assembling with rRNA to construct ribosomes for new protein synthesis, ribosomal proteins are known to have many extraribosomal roles [12][14]. One of the ribosomal proteins, ribosomal protein S27-like (RPS27L), was reported to be downregulated in feces and tumor tissues of some late-stage CRC patients [15], [16].…”
Section: Introductionmentioning
confidence: 99%